2011
DOI: 10.1007/s11999-010-1558-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Reasons for Nonrevision Reoperation After Total Knee Arthroplasty

Abstract: Background A dramatic increase in the demand for TKA is expected. The current burden of revision TKA is well known but the incidence and etiology of nonrevision reoperations after primary TKA is not. Questions/purposes We determined the rate, reason, timing, and predictors of nonrevision reoperation after TKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 20 publications
2
38
0
2
Order By: Relevance
“…The most common reason for unplanned readmission following total knee arthroplasty in the present study was stiffness (2.7%, 141 of 5207). A previous study from our institution likewise demonstrated that the most common reason for reoperation within one year following this procedure was stiffness, with >58% of the non-revision reoperations (involving 2.3% of all total knee arthroplasties) being manipulation under anesthesia 6 . Overall, the most common cause of unplanned readmission following total joint arthroplasty in the present study was joint-related infection (1.4%, 150 of 10,633).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…The most common reason for unplanned readmission following total knee arthroplasty in the present study was stiffness (2.7%, 141 of 5207). A previous study from our institution likewise demonstrated that the most common reason for reoperation within one year following this procedure was stiffness, with >58% of the non-revision reoperations (involving 2.3% of all total knee arthroplasties) being manipulation under anesthesia 6 . Overall, the most common cause of unplanned readmission following total joint arthroplasty in the present study was joint-related infection (1.4%, 150 of 10,633).…”
mentioning
confidence: 64%
“…With this projected exponential growth in total joint arthroplasty, there are concerns of an overwhelming workload for the medical community and an increasing financial burden on society 4 . Despite the great success of arthroplasty, complications associated with surgery occur, leading to prolonged inpatient care, hospital readmission, or even reoperation [5][6][7][8] . Minimization of such complications, always an important goal for patients and their surgeons, would have a major impact on reducing the health-care burden.…”
mentioning
confidence: 99%
“…One patient in both the experimental and the control groups (1.3%) required irrigation and débride-ment with tibial polyethylene exchange for persistent wound drainage/hematoma evacuation; however, of the entire cohort of 150 patients, this would be within the historically typical range for a reoperation rate at our institution after TKA [34]. In addition, the incidence of manipulation under anesthesia for postoperative stiffness/ arthrofibrosis was 4% (three patients of 75 total) in the experimental group and 6.7% (five patients of 75 total) in the control group.…”
Section: Discussionmentioning
confidence: 96%
“…According to gait analyses and biomechanical studies, patients require at least 83°of flexion to ascend stairs, 90°to 100°to descend stairs, 93°to 105°to rise from a standard or short chair, and more than 115°to squat or kneel [3,11,13]. However, up to 20% of patients may develop knee stiffness and achieve knee flexion of less than 90°after their index arthroplasty [12,17,19,28]. If left untreated, knee stiffness reduces the functional outcomes of patients including their daily living activities and satisfaction [25,26].…”
Section: Introductionmentioning
confidence: 99%